To rearrange the equation \( G = H - TS \) for \( T \), we can start by isolating \( T \).
- Rearranging the equation gives us \( TS = H - G \).
- Next, we divide both sides by \( S \) to solve for \( T \):
\[ T = \frac{H - G}{S} \]
This means that none of the provided options perfectly fit this derived equation. However, if you look at option \( T = \frac{G - H}{S} \), it's the negative of the correct arrangement.
To summarize:
- Start with the equation: \( G = H - TS \)
- Rearrange:
- Add \( TS \) to both sides: \( G + TS = H \)
- Then rearrange to isolate \( T \): \( TS = H - G \)
- Finally, divide by \( S \): \( T = \frac{H - G}{S} \)
To emphasize the correct rearrangement:
The correct equation for \( T \) is: \[ T = \frac{H - G}{S} \]
If you need to select the closest one, it would be none specifically listed unless you re-check, but if given the option again, keep in mind the math leading to \( T = \frac{H - G}{S} \).